2013
DOI: 10.1371/journal.pone.0065464
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Wild Mammal Assemblages along an Urban–Rural–Forest Landscape Gradient in Warm-Temperate East Asia

Abstract: Urbanization may alter mammal assemblages via habitat loss, food subsidies, and other factors related to human activities. The general distribution patterns of wild mammal assemblages along urban–rural–forest landscape gradients have not been studied, although many studies have focused on a single species or taxon, such as rodents. We quantitatively evaluated the effects of the urban–rural–forest gradient and spatial scale on the distributions of large and mid-sized mammals in the world's largest metropolitan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 74 publications
3
43
1
1
Order By: Relevance
“…Boxplots of the relative abundances of the most dominant bacterial phyla (a) and fungal classes (b) show no significant differences in relative abundance between parks (black) and medians (gray). Saito and Koike, 2013;Concepción et al, 2015), we re-acknowledge that many macroorganisms decline in diversity in cities relative to rural areas and that some species are absent in cities, resulting in changes in composition. Recent work (Beninde et al, 2015) has surveyed the causes of intra-urban biodiversity variation for a range of macroorganisms and found that, to a great extent, shifts in composition and declines in diversity in cities are due to the effects of habitat area and connectivity, with the most affected green spaces in cities being both small and disconnected.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Boxplots of the relative abundances of the most dominant bacterial phyla (a) and fungal classes (b) show no significant differences in relative abundance between parks (black) and medians (gray). Saito and Koike, 2013;Concepción et al, 2015), we re-acknowledge that many macroorganisms decline in diversity in cities relative to rural areas and that some species are absent in cities, resulting in changes in composition. Recent work (Beninde et al, 2015) has surveyed the causes of intra-urban biodiversity variation for a range of macroorganisms and found that, to a great extent, shifts in composition and declines in diversity in cities are due to the effects of habitat area and connectivity, with the most affected green spaces in cities being both small and disconnected.…”
Section: Discussionmentioning
confidence: 91%
“…This stress is predicted to reduce diversity beyond the predicted reduction owing to small habitat patch size, while intermediate disturbances (for example, suburban development) may lead to local diversity peaks. Plant and animal communities often show these expected patterns of intermediate optima, while minimal diversity is seen in the most urbanized sites (for example, Blair, 1996;Blair and Launer, 1997;Cam et al, 2000;Marzluff, 2005;McKinney, 2008;Minor and Urban, 2010;Saito and Koike, 2013). Response to urbanization varies within a city depending on site characteristics (Sushinsky et al, 2013) as well as on the species assemblage and the spatial scale investigated (Concepción et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Bogotá Additionally, monitoring mammal diversity and activity patterns is important due to the relationships of these animals with anthropogenic dynamics, as supported by evidence outside and inside protected areas affected by human presence (Ordeñana et al 2010, Lira-Torres & Briones-Salas 2012, Gonthier & Castañeda 2013, Lynam et al 2013, in agriculture lands near forests (Cove et al 2013), in interfaces between rural and urban areas (Abi Said & Amr 2012, Saito & Koike 2013, as well as in relation with the presence of exotic species (Ordeñana et al 2010, Lenth et al 2008. Therefore, monitoring species community diversity and activity patterns are fundamental aspects when evaluating species vulnerability within a protected area.…”
Section: Monitoring Program For Mammals In a Protected Area Of Colombmentioning
confidence: 99%
“…This evidence is essential to predict changes in populations and communities in space and time, as well as to identify the threats they face (Salom-Pérez et al 2007, Ordeñana et al 2010, Sathyakumar et al 2011, Gonthier & Castañeda 2013, Saito & Koike 2013, in order to implement timely and appropriate management actions (Sathyakumar et al 2011, Lira-Torres & BrionesSalas 2012, Saito & Koike 2013.…”
Section: Monitoring Program For Mammals In a Protected Area Of Colombmentioning
confidence: 99%
“…Logo, a ocorrência dessas espécies está fortemente relacionada às características ambientais das áreas que habitam. Por conta disso, busca-se compreender qual a influência da paisagem sobre a ocorrência destas (LYRA-JORGE et al, 2010;BITETTI, 2011;SAITO;KOIKE, 2013), para guiar ações de conservação.…”
Section: Introductionunclassified